Assessing Creativity in Secondary Schools: A Focus on the Impact of an Arts‐based Intervention. (16th April 2022) - Briguglio, Marie; Baldacchino, Leonie; Mangion, Margaret
Abstract: As programs aimed at fostering creativity in educational settings become more widespread, assessing their impact becomes increasingly important. This article responds to calls for evidence‐based policy in this field by assessing the impact on creativity of a government‐funded arts‐based educational program in Malta (European Union). A quasi‐experimental design was adopted and data was collected pre‐ and post‐intervention from a test group and a control group of students across nine secondary schools ( n = 400 pre‐intervention and n = 259 post‐intervention). Students undertook a total of four Divergent Thinking tests, which culminated in indices comprising ideational fluency, flexibility, originality, novelty, relevance, and elaboration. Ordinary Least Squares models of creativity were estimated revealing a strong positive association between creativity scores and participation in the program. Difference‐in‐Differences analyzes with matched pre‐ and post‐intervention responses ( n = 380), further confirmed that participation in the program positively impacts creativity scores, particularly among students who did not self‐select into the project and who had low prior exposure to creative experiences. We also observe an overall decline in creativity between the start and end of the scholastic year. These results suggest that arts‐based programs can be effective in enhancing (at worst, preserving) students' creativity.